(untitled) (Asian Education Studies, 2026)
Science education in the United States has undergone a profound shift in emphasis away from lecture-based and knowledge-based approaches towards more hands-on platforms with emphasis on skill training and maximizing feedback. Of central importance in this movement has been the concept of scientific teaching: the idea of treating education like a scientific subject by performing experiments on educational outcomes. In the last two decades, a wealth of research has been conducted using this principle to examine the effectiveness of a wide range of pedagogical techniques. Of the many methods used to deliver class content to students, active learning has emerged as one of the most powerful. Another critical development in scientific teaching has been the realization of a wide range of standardized assessment tools for quantifying various student outcomes. Despite the convincing nature of empirical evidence in favor of the utility of both scientific teaching and active learning, dissemination of these platforms in average teaching practices has been slow, even in the US. This article reviews the many advances and challenges of scientific teaching reform, ending with a brief commentary of reform experiences in the US and how these may impact East Asia in the near future.